INTEGRATION OF UKRAINIAN INDUSTRY SCIENTIFIC PERIODACLS INTO WORLD SCIENTIFIC INFORMATION SPACE: PROBLEMS AND SOLUTIONS - T. O. Kolesnykova (Nauka ta progres transportu, 2013)
Purpose. Problem of representation lack of scientists’ publications, including transport scientists, in the international scientometric databases is the urgent one for Ukrainian science. To solve the problem one should study the structure and quality of the information flow of scientific periodicals of railway universities in Ukraine and to determine the integration algorithm of scientific publications of Ukrainian scientists into the world scientific information space. Methodology. Applying the methods of scientific analysis, synthesis, analogy, comparison and prediction the author has investigated the problem of scientific knowledge distribution using formal communications. The readiness of Ukrainian railway periodicals to registration procedure in the international scientometric systems was analyzed. The level of representation of articles and authors of Ukrainian railway universities in scientometric database Scopus was studied. Findings. Monitoring of the portals of railway industry universities of Ukraine and the sites of their scientific periodicals and analysis of obtained data prove insufficient readiness of most scientific publications for submission to scientometric database. The ways providing sufficient "visibility" of industry periodicals of Ukrainian universities in the global scientific information space were proposed. Originality. The structure and quality of documentary flow of scientific periodicals in railway transport universities of Ukraine and its reflection in scientometric DB Scopus were first investigated. The basic directions of university activities to integrate the results of transport scientists research into the global scientific digital environment were outlined. It was determined the leading role of university libraries in the integration processes of scientific documentary resources of universities into the global scientific and information communicative space. Practical value. Implementation of the proposed activity algorithm of Ukrainian universities to integrate the scientific publications into the world digital environment will increase the importance of Ukrainian scientific periodicals, including the railway ones, affect the positive dynamics in the university rating, strengthen the authority Ukrainian science in the world and attract potential investors.